Analysis of the E-Master Application as an Effort of Employment Data Processing - Novita, Triske; Puspasari, Durinta (Economic Education Analysis Journal, 2021)
This study aimed to analyze the E-Master application as an effort to process personnel data. This research type was descriptive qualitative. The research subjects were 5 people consisting of 2 OTKP teachers and 3 administrative employees at SMKN 10 Surabaya, while 2 administrative employees and 1 Head of Study Program as source triangulation. Data collection techniques were questionnaires and interviews, while data analysis techniques used data condensation, data presentation, drawing conclusions. The results of the study showed: (1) mapping indicators were able to map Civil servant; (2) SKP indicators, could be used as a medium for monitoring the performance of each Civil servant; (3) training analysis indicators, Civil servant could take part in training activities; (4) promotion indicators, making it easier for Civil servant during the promotion process; (5) pension indicator, providing a sufficient period of time in managing pension files; (6) periodic salary indicators, facilitating the finance department in processing periodic salary calculations; (7) Taspen indicator, making it easier for staffing department to process data on retired personnel; (8) Leave indicators, it was easier for staffing officers to print Civil servant attendance lists; (9) Study permit indicator, helping Civil servant if they wanted to continue their education again.